Am I the only sane one working here? [electronic resource] : 101 solutions for surviving office insanity - Bernstein, Albert J. (McGraw-Hill, 2009)
From a bestselling psychologist with an expertise in office-survival comes an indispensable guide to triumphing over the 101 situations in the workplace that can drive you absolutely up the wall.